BERTEOLOGI MORAL KONTEKSTUAL DI INDONESIA BERDASARKAN ETIKA KOMUNITARIAN BENEZET BUJO - Yohanes Yupilustanaji Apgrianto (P3TK, Sanata Dharma University, 2012)
The main purpose of this article is to search for a profound understanding about the bay of doing an effective and efficient contextual moral theology in the face a concrete social problem. To reach that goal, this articles discusses the work of Benezet Bujo, an African moral theology who tries to think about the way to do contextual moral theology in African context. Methodologically, this articles starts from Benezet Bujos critical view of the implementation of Western morality which is not obly entirely incompatible with African society, but also very often harmful to them.Concretely, Benezet Bujo propose an African Communitarian Ethics implementation. This article will discuss the idea of African Communitarian Ethics more deeply and also stresses that the moral theological principles of African Communitarian Ethics help us understand the method of doing contextual theology which is more profound, effective, and efficient in the face of social problems in our society.